Representation Of Women In Selected Television Dramas Across Different Political Regimes In Pakistan - Ahmed, Shumaila (2018)
Media has a prominent and important role in the representation of different groups, classes and genders in a society. This study aims to examine the representation of women in the television dramas across four different political ruling regimes in Pakistan. The relationship of policies and programs of political ruling governments with the ideology of patriarchy is observed from the representation of women and issues of violation of women’s rights in the television drama. From the Marxist feminist theoretical perspective, the relationship between the hegemony of powerful ruling class and the ideology of patriarchy to the exploitation of a subordinate class of women is examined.